1981
DOI: 10.1007/bf00558383
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in the pharmacokinetics of digitoxin and digoxin during long-term treatment

Abstract: Patients suffering from congestive heart failure received maintenance doses of digitoxin (N = 10) or digoxin (N = 8). The plasma glycoside concentration was determined, and after a single dose of 3H-digitoxin or 3H-digoxin, the decline and excretion of radioactivity were measured over a period of 7 (digitoxin) and 3 days (digoxin). Plasma radioactivity declined with a T1/2 beta between 77 and 234 h (mean 138 h) in the case of digitoxin and with a T1/2 beta between 9.2 and 38.6 h (mean 23.5 h) for digoxin. A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Consistent with prev ous studies of digitoxin (Perrier et al, 1977;Ochs et al, 1980b;Haustein, 1981;Vohringer & Rietbrock, 1978), elimination half-life is very long, averaging 8 days in the present study. Digitoxin volume of distribution averaged 0.76 1/kg.…”
Section: Multiple-dose Kineticssupporting
confidence: 92%
“…Consistent with prev ous studies of digitoxin (Perrier et al, 1977;Ochs et al, 1980b;Haustein, 1981;Vohringer & Rietbrock, 1978), elimination half-life is very long, averaging 8 days in the present study. Digitoxin volume of distribution averaged 0.76 1/kg.…”
Section: Multiple-dose Kineticssupporting
confidence: 92%
“…The plasma half-life after administration of radioactive labelled digitoxin was shown to be about 77-234 h (mean 138 h) [33]. In a status of normal liver and kidney function, 60% of digitoxin is eliminated via urine, about half of it as conjugated metabolites, and about 40% is excreted via faeces, partly secreted via bile and partly directly through the mucosal wall [34].…”
Section: Eliminationmentioning
confidence: 99%
“…When kidney function is impaired and renal elimination of digitoxin is reduced, this is compensated by increased metabolization and excretion via the faeces [36,37]. Several authors reported a reduced half-life of digitoxin in patients with kidney malfunction rather than a prolonged one as compared with patients with normal renal function [29][30][31][32][33][34][35][36][37][38][39][40][41]. Also, patients with hepatic insufficiency or with hepatic and renal malfunction showed no significant changes in elimination half-life [20,42].…”
Section: Eliminationmentioning
confidence: 99%